Interleukin-18-deficient mice develop hippocampal abnormalities related to possible depressive-like behaviors. (1st June 2019) - Yamanishi, Kyosuke; Doe, Nobutaka; Mukai, Keiichiro; Ikubo, Kaoru; Hashimoto, Takuya; Uwa, Noriko; Sumida, Miho; El-Darawish, Yosif; Gamachi, Naomi; Li, Wen; Kuwahara-Otani, Sachi; Maeda, Seishi; et al.
Abstract: Interleukin-18 (IL-18) is an inflammatory cytokine linked to major depressive disorder (MDD). MDD is closely related to metabolic disorders, such as diabetes mellitus (DM) and obesity. Moreover, DM is associated with cognitive impairment and promotes apoptosis of hippocampal cells by activating pro-apoptotic and inhibiting anti-apoptotic factors. IL-18-deficient ( Il18 −/− ) mice are obese and have DM. Therefore, we hypothesized a close relationship between IL-18 and death of hippocampal cells, affecting neurogenesis related to behavioral changes such as MDD. Il18 −/− male mice were generated on the C57Bl/6 background and Il18 +/+ mice were used as controls. Behavioral, histopathological, and molecular responses, as well as responses to intracerebral recombinant IL-18 administration, were examined. Compared with Il18 +/+ mice, Il18 −/− mice had impaired learning and memory and exhibited lower motivation. In the Il18 −/− mice, degenerated mitochondria were detected in synaptic terminals in the molecular layer, the polymorphic layer, and in mossy fibers in the dentate gyrus, suggesting mitochondrial abnormalities. Because of the degeneration of mitochondria in the dentate gyrus, in which pro-apoptotic molecules were upregulated and anti-apoptotic factors were decreased, apoptosis inducers were not cleaved, indicating inhibition of apoptosis. In addition, neurogenesis in the dentate gyrus and the maturity of neuronal cells were decreased in the Il18 −/− mice, while intracerebral administration of recombinant IL-18 promoted significant recovery of neurogenesis. Our findings suggested that IL-18 was indispensable for mitochondrial homeostasis, sustaining clearance of degenerative neural cells, and supporting neurogenesis, normal neuronal maturation and hippocampal function. Highlights: IL-18 deficient mice showed behavioral changes, such as impairment of learning and memory. IL-18 dysfunction induced hippocampal impairment. IL-18 deficiency led to mitochondrial degeneration in hippocampus, especially in presynaptic terminals of the dentate gyrus. IL-18 impairment inhibited neurogenesis and maturation in the dentate gyrus of the hippocampus. Intracerebral IL-18 injection rescued some aspects of the neuronal maturation process in the dentate gyrus.